Traditional and complementary medicine use among chronic haemodialysis patients: a nationwide cross-sectional study - Zakaria, Nor Fadhlina; Mohd Noor, Mohd Tawfeq; Abdullah, Rafidah (Springer, 2021)
Background: In the era of digital and improved conventional medicine, many continue to use traditional and complementary medicine (TCM). The prevalence of its usage is not well reported, especially in patients with end-stage kidney disease (ESKD) receiving haemodialysis, thus its benefits and adverse effects are not widely known. This study determines the prevalence, types, perceptions and factors associated with TCM use by chronic haemodialysis patients in Malaysia. Methods: This is a multi-centre cross-sectional study involving patients undergoing haemodialysis treatment in Malaysia. A validated face-to-face questionnaire-based interview was conducted. Sociodemographic and clinical profiles of the patients, factors associated with TCM use, perceptions, sources of information, and disclosures to treating doctors were obtained. Data were analysed using SPSS software. Results: A total of n = 329 participants were recruited. The mean age of the participants was 54.9 ± 12.5 years. The majority were Malays (72%) and females (54.7%). A total of 64.7% (n = 213) reported TCM use; n = 132 used TCM before the initiation of dialysis, while n = 81 used TCM after initiation. In the post-hoc analysis, patients who had never used TCM had a higher mean age (56.7 ± 12.3 years) than the patients who used TCM (51.1 ± 13.1) (p = 0.015) and were likely to have received primary education (p = 0.011). Unemployment was more likely to be associated with non-TCM use; with odds ratio 1.85 (95% CI: 1.15, 2.98). Biologically based therapy was found to be the most popular (97.2%) type of TCM, including herbal medicine (67.6%) and supplements (58.0%). Most respondents did not disclose their TCM use to their doctors (72.3%), and 41.8% had the perception that they felt better. Conclusions: TCM is widely used among chronic haemodialysis patients in Malaysia, mainly herbal medicine and supplements. Non-disclosure to healthcare professionals and a poor monitoring and regulation of its use in ESKD patients could be detrimental. Awareness needs to be raised among healthcare professionals and the general population.